P4 Patient and Carer Co-investigators: Shared experiences of a Research Steering Group from the Idiopathic Pulmonary Fibrosis Patient Reported Outcome Measure (IPF-PRoM) study. (12th November 2015) - Russell, AM; Doyle, AM; Ross, D; Burdett, C; Gane, J; Fleming, S; Aden, Z; Maher, TM; Cullinan, P
Abstract : Introduction: The IPF-PROM development project sought to integrate patients and carers both as participants and co-investigators in the research process. Patients with varied experiences of IPF and members of the multidisciplinary team including a clinical psychologist; research nurses, Patient and Public Involvement Lead and a carer formed the IPF-PROM Research Steering Group (RSG) at the outset of the study. Methodology: Fundamental to PROM development is a robust approach to the item generation process to support the final conceptual framework. The RSG had a key role to ensure patient language was accurately represented. All RSG members: Agreed formal terms of reference and role descriptions. Reviewed the study protocol. Analysed 5 focus groups transcripts individually and collectively identified themes. Applied consensus methods to a list of pooled items collated from questionnaires that have been used in studies in IPF populations. Assessed the face validity of an electronic Delphi survey administered to patients, carers and healthcare professionals in the UK. Analysed the free-text comments captured in the Delphi study using a thematic approach. Participated in a Reflective exercise to characterise individual's perceptions and motivations for continuing involvement in the RSG. Results: RSG members contributed a level of sympathy, insight, compassion and knowledge to the thematic analysis of the focus groups: a dynamic that enhanced the interpretation of transcripts. Emotions evoked by the transcripts were 'therapeutic' rather than 'distressing'. 200 statements were identified for inclusion in the Delphi. Patient and carers added new and different perspectives on the use of language; rich discussion preceded consensus. Items identified in existing questionnaires (n = 315) were reduced (n = 58). An additional 18 items were discussed and modified prior to inclusion in the Delphi. Several themes were identified following the reflective exercise encapsulating the group experience. Motivation to work in the RSG whether professionally or personally driven felt complementary, resulting in a sense of connexion; personal/professional belonging and learning together (Table 1 ). Discussion: We advocate the RSG model as feasible, sustainable and enriching component of the research experience, specifically in PRO development to enhance content validity. Participating in group reflection has enhanced our understanding of the RSG dynamic.